2020
DOI: 10.1016/j.jacbts.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Septal Reduction Using Transvenous Intramyocardial Cerclage Radiofrequency Ablation

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…To the best of our knowledge, this study represents the first description of percutaneous ultrasound-guided RFA of CDs in either veterinary or human medicine. In humans, this technique has been used to alleviate myocardial hypertrophy [58][59][60] and to treat neuroendocrine tumors, such as paragangliomas, in different locations [61][62][63]. Percutaneous ultrasound-guided RFA has been reported for treatment of parathyroid and thyroid masses in dogs [42][43][44][45] and cats [46], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study represents the first description of percutaneous ultrasound-guided RFA of CDs in either veterinary or human medicine. In humans, this technique has been used to alleviate myocardial hypertrophy [58][59][60] and to treat neuroendocrine tumors, such as paragangliomas, in different locations [61][62][63]. Percutaneous ultrasound-guided RFA has been reported for treatment of parathyroid and thyroid masses in dogs [42][43][44][45] and cats [46], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, septal para-hisian pacing has been proposed as an alternative treatment option employing a similar approach. Imaging guidance, particularly through preprocedural cardiac CT scans, plays a pivotal role in visualizing the anatomy of septal veins [ 5 , 6 , 7 ]. It serves as a key imaging tool for determining and planning the procedure in advance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies that attempt to approach the ventricular septum through the septal perforator vein are introduced [ 6 , 7 ]. A study had examined the trans-coronary intraseptal RF ablation technique in the treatment of HOCM [ 8 ], which had shown that the utilization of the Thru-Septal RF ablation was eligible for evaluation in a clinical trial. However, Thru-Septal technologies are dependent on the septal perforator vein anatomy in approaching the basal interventricular septum (IVS) from the distal part of the coronary sinus.…”
Section: Introductionmentioning
confidence: 99%